Locating the Ideal State: The Practice of Place by Far Right and Islamist Parties - Heupner, Susan de Groot (Journal of intercultural studies, 2023)
This article explores the co-constitutive practice and conceptualisation of place in political parties at opposite ends of the ideological spectrum. Illustrated with examples from the Islamist Hizb ut-Tahrir in Denmark (DK) and the Netherlands (NL) and the far right Party for Freedom (NL) and the Danish People’s Party (DK), we seek to better understand the role of place and space in the translation of ideology to practice. With the concept of lived space central to our argument, we propose that ‘ideal places’ – be they Caliphates or ethnically and religiously homogeneous nation-states – are precisely co-constitutive in that one party’s utopia is the other’s dystopia. However, pointing to the essence of co-constitutive opposing ideals does not suffice when addressing members, recruits, voters, or wider audiences; ideals must be realised, enacted or performed in order to move, drive and inspire people. Thus, we ask, how do political parties turn ideals into something tangible and practicable? Our argument is that a better understanding of the role of place through the concept of lived space helps explain the apparent success of ideologically driven non-conformist parties in Western Europe.